Unraveling the puzzling risk–return relationship: Distinctive roles of government involvement in venture capital investment - Zhang, Jiamin; Gu, Qian Cecilia (Strategic Management Journal, 2024)
Abstract Research Summary Government involvement plays a significant role in fostering entrepreneurship. We examine how government involvement in venture capital (VC) investments shapes the decoupling between risk‐taking and investment returns. We distinguish government involvement through state ownership (GVC) and personal political connections (connected VC). We theorize that government involvement through GVC is associated with the downside risk–return paradox, that is, concurrent higher risk‐taking and lower‐than‐expected returns. In contrast, government involvement through connected VCs is linked to the upside risk–return paradox, that is, concurrent lower risk‐taking and higher‐than‐expected returns. Our theoretical predictions receive general support from analyses using longitudinal data from VC firms in China. Our study sheds light on the heterogeneity in the decoupling between risk and return and the underlying mechanisms through which governments influence entrepreneurship. Managerial Summary Governments often seek to promote entrepreneurship; yet, their involvement in start‐ups tends to deviate from the conventional wisdom of a positive risk–return association. Government‐owned venture capital (VC) firms tend to take greater risks and invest in earlier‐stage start‐ups, but yield lower returns from their investments. Conversely, VC firms that have personal ties to government officials tend to take lower risks and prefer later‐stage start‐ups, yet achieve higher returns. These intriguing findings reveal the complexities of government participation in entrepreneurial activities and offer valuable insights for policy formulation. In addition, our findings highlight the importance for entrepreneurs to recognize diverse goals and resources in government involvement. Considering this when seeking external financing is helpful in positioning start‐ups for growth and success.